2019
DOI: 10.1186/s13012-018-0842-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the Exploration, Preparation, Implementation, Sustainment (EPIS) framework

Abstract: BackgroundEffective implementation of evidence-based practices (EBPs) remains a significant challenge. Numerous existing models and frameworks identify key factors and processes to facilitate implementation. However, there is a need to better understand how individual models and frameworks are applied in research projects, how they can support the implementation process, and how they might advance implementation science. This systematic review examines and describes the research application of a widely used im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
649
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 684 publications
(730 citation statements)
references
References 77 publications
15
649
0
7
Order By: Relevance
“…Themes in this study heavily aligned with the outer context, similar to the emerging literature on policy determinants (8,36,37). However, a recent systematic review of the EPIS framework review found it makes up a lower proportion of implementation research overall (23).…”
Section: Conclusion Main Findingssupporting
confidence: 63%
See 1 more Smart Citation
“…Themes in this study heavily aligned with the outer context, similar to the emerging literature on policy determinants (8,36,37). However, a recent systematic review of the EPIS framework review found it makes up a lower proportion of implementation research overall (23).…”
Section: Conclusion Main Findingssupporting
confidence: 63%
“…Continued research must focus on improved understanding of organizational and political drivers of sustainment (4,5,23,44). The eld of addiction policy needs sustainment strategies developed from an understanding of key drivers (24,41,44,45).…”
Section: Limitations and Next Stepsmentioning
confidence: 99%
“…Sociopolitical and funding issues, client advocacy, and interorganizational networks formed part of the outer context, whereas organizational characteristics, leadership, and individual adopter characteristics made up the inner context, with specific aspects of each affecting each of the phases. It is interesting to note that adaptation was identified as a necessary component of EPIS with respect to the outer and inner contexts, as well as to the implementation of the EBP 51 …”
Section: Discussionmentioning
confidence: 99%
“…Project ImPACT for Toddlers (PI T ) was adapted specifically for toddlers 12‐36 months of age through a collaborative community partnered participatory research process by a group of researchers, providers, funders, and parents of children with ASD known as the BRIDGE Collaborative (Brookman‐Frazee, Stahmer, Lewis, Feder, & Reed, 2012; Rieth, Stahmer, et al, 2018; Stahmer et al, 2017). The team applied the exploration, preparation, implementation, sustainment (EPIS) framework (Aarons, Hurlburt, & Horwitz, 2011; Moullin, Dickson, Stadnick, Rabin, & Aarons, 2019) to guide adaptation efforts. In addition to specifying four distinct phases of the implementation process, EPIS identifies outer and inner context factors that are key to implementation.…”
Section: Introductionmentioning
confidence: 99%